The role of stakeholder participation in wetland conservation in urban areas: A case of Monavale Vlei, Harare - Tatenda Musasa; Kudakwashe C. R Muringaniza; Munaishe Manyati (Elsevier, 2023)
Wetland ecosystems are highly complex in production and the extent of plant and animal diversity. The study assessed the role that various stakeholders play in the sustainable use and conservation of particularly urban wetlands. The specific objectives of the study were to establish threats to the sustainable use of the Monavale Wetland; determine wetland conservation strategies adopted; and examine the role of stakeholders in wetland use and conservation. This study adopted a combination of quantitative and qualitative research methods to expand and enhance the quality of the results obtained. A questionnaire was adopted to collect data from 90 household heads or their proxies using random sampling. Additionally, semi structured interviews were used to obtain information from Environmental Management Agency (EMA), Conservation Society of Monavale (COSMO) and Ramsar Zimbabwe. Qualitative data were analysed using the content analysis method whereas descriptive and inferential statistics were used for quantitative data. Findings demonstrate that 63% agreed that the government has fostered and strengthened private partnerships that benefit the wetland. Only 40% of respondents from Monavale agreed that the local government has developed effective conservation policies. Residents in the areas surrounding the marsh were named as stakeholders by 98% of those who responded to the questionnaires. In conclusion, the research shows that stakeholders play a pivotal and essential role in wetland use and conservation if sustainability is to be achieved. The study therefore recommends that the Government invests in programs that involve various stakeholders in policy development and implementation. This study will at the end propose a framework to enhance sustainable use of wetlands and proffer wetland conservation.